Macroeconomic adjustment to monetary union - Gabriel Fagan; Vítor Gaspar (European Central Bank (ECB), 2008)
The move to monetary union in Europe led to convergence of interest rates among the participating countries. This was associated with notable cross-country differences in the behaviour of key macroeconomic aggregates. Compared to the low interest rate countries, former high interest rate countries experienced a boom in domestic demand, a deterioration of the current account and appreciation of the real exchange rate. This paper documents the key stylised facts of this experience and provides a compact two-country model, based on the Blanchard-Yaari setup, to analyze this phenomenon. This model, though simple, is able to broadly capture the main qualitative features of the adjustment. Using this model, we show that the creation of the monetary union leads to an increase in welfare for all generations in both country groups.
Keywords: F36; E21; F32; 330; euro area; interest rate convergence; overlapping generations model; Zinsstruktur; Wirtschaftliche Konvergenz; Eurozone; Wirkungsanalyse; Overlapping Generations; Theorie; EU-Staaten